Long term predictors of adherence to Antiretroviral Therapy for HIV positive adults at Felege-Hiwot Teaching and Specialized Hospital, North-West Ethiopia: a transitional study - Seyoum, Awoke; Ndlovu, Principal; Zewotir, Temesgen (Ethiopian Journal of Science and Technology, 2025)
In clinical trials and practices, failure of adherence to medications is a common challenge among patients with chronic diseases. Many factors are associated with this failure. Reports of previous studies about predictors of adherence to Highly Active Antiretroviral Therapy (HAART) were not consistent. The main objective of this study was to identify predictors of long-term adherence to HAART, considering lag variables as additional predictors. Transitional modeling was used to determine the predictors of long-term adherence to HAART. A retrospective transitional study design was conducted on 792 randomly selected adult patients at Felege-Hiwot Teaching and Specialized Hospital, Bahir Dar, Ethiopia. Results revealed that the first two lag-variables ( ) were significantly associated with performance of current adherence to HAART. The increase in CD4 cell count change was significantly associated with current adherence, if patients made transition from adherent level at lag2 to non-adherent level at lag1 ( ). As a conclusion, for patients who were transferred from adherent level at lag2 to non-adherent level at lag1, their CD4 cell count changes were positively correlated with current adherence level. Due attention should thus be given to address the specific needs of each group of patients. Non-adherence to HAART in this long-term treatment program was at risk and should receive interventional action. Educational therapy during follow-ups should also be given to non-adherent patients to strengthen the era of long-term treatment.